2021 Comprehensive Surveillance Review : Overview Paper. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2021)
Fund surveillance needs to evolve to face the economic and financial challenges that will shape the global landscape for years to come. This paper first takes stock of the current economic and financial landscape. To better serve the membership in this context, Fund surveillance should be prioritized around four key priorities: (i) confronting risks and uncertainties: policymakers will need to actively manage the risks of a highly uncertain outlook; (ii) preempting and mitigating adverse spillovers: shifting patterns of global economic integration will bring about new channels for contagion and policy spillovers; (iii) fostering economic sustainability: a broader understanding of sustainability to better account for the impact of economic and non-economic developments on stability; and (iv) unified policy advice: better accounting for the trade-offs and synergies among different policy combinations in the face of limited policy space and overlapping priorities, tailored to country-specific circumstances. These priorities should further enhance the traction of Fund surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Externalities; Monetary Policy; Political Economy